Deltagelsens kunst? - Schwarzbart, Judith; Samson, Kristine (K&K - Kultur og Klasse, 2014)
Within recent years, art and urbanism have gradually moved closer to each other and come together around socially engaged, dialogical projects. Participation and the creation of urban publics are topics that often concern artists as well as urban planners and activists. Based on a record of this recent conjunction between art and urbanism, the article examines practices, fractures, and conflicts in the aftermath of the social turn. With a point of departure in the coalescing public programme of the Istanbul Biennial and Occupy Gezi at Taksim Square in 2013, the article questions the art of participation. What type of public is created in the participative art? And is an artistic social turn towards the city even possible beyond the art institution? The article concludes that precisely in the conflict between the two different rationales of art and urbanism a participatory, urban public can emerge; a public, however, which lie beyond the intention and rationales of the individual actor.